The Impact of Intellectual Capital (Mvaic) on Financial Leverage in the Asean Telecommunication Industry: The Mediating Role of Firm Profitability - Marta KN Pasaribu; Isfenti Sadalia; Nisrul Irawati (Indonesian Journal of Business Analytics, 2025)
Intellectual Capital (IC) significantly enhances financial performance and influences capital structure. This study examines IC's impact on financial leverage using the Modified Value Added Intellectual Coefficient (MVAIC), mediated by firm profitability. IC components—Human Capital Efficiency (HCE), Structural Capital Efficiency (SCE), Relational Capital Efficiency (RCE), and Capital Employed Efficiency (CEE)—are analyzed in 120 ASEAN telecommunication firms through panel data regression. Findings confirm IC positively affects profitability (ROA), supporting Resource-Based Theory, while profitability negatively influences financial leverage (DAR), aligning with Pecking Order Theory. Among IC components, only CEE significantly impacts ROA and DAR via profitability mediation. Firms with high capital efficiency achieve better profitability and lower external debt dependence, emphasizing IC management for financial stability.